THE INFLUENCE OF SOIL MULCHING ON GROWTH AND YIELD OF TWO STRAWBERRY VARIETIES - Zuhair A. Dawood (Mesopotamia Journal of Agriculture)
This research was conducted at the Department of Horticulture science and landscape design College of Agriculture and forestry Mosul University , Iraq, during the growing season 2006-2007 this study was to investigate the effect of soil mulching on growth and yield of two varieties of Strawberry (Hapil and Kaisers samling) and three types of mulches (Polyethylene, black plastic and straw) were used in addition to control (without mulching).The experiment design was split-split plot within (RCBD) with three replicates , each experimented unit included 9 plants, all results were tested by using Duncan's multiple range test at probability of 5%.The obtained results could be summarized as follows: Most vegetative growth and yield characteristics were significantly increased in Hapil variety as compared with Kaisers samling variety. Soil mulching by three types of mulches caused a significant increased in leaf area and number of stolen per plants. Average weight of fruit increased significant by straw mulching. The highest percentage of (TSS) recorded by black plastic mulching, at the same time, soil mulching by Polyethylene caused a significant increased in number of flowers per plants. There was different effects of interaction treatments between types of mulches and variety on vegetative, flowering growth and yield characteristics.